DIET OF THE BROWN HOWLER MONKEY ALOUATTA-FUSCA IN A FOREST FRAGMENT IN SOUTHEASTERN BRAZIL - Galetti, M.; Pedroni, F.; Morellato, LPC (Museum Nat Hist Naturelle, 1994)
The diet of the brown howler monkey Alouatta fusca in a 250 ha forest fragment in southeastern Brazil was studied for 42 consecutive months. The howlers were observed eating in 366 feeding records (one group or a monkey eating a single plant) of 52 plant species. Twenty three percent of the leaves and 52 % of the flowers in the howler's diet came from lianas. Eighteen fruit species were recorded as being dispersed by howlers and seeds of two liana species were eaten. In small forest fragments where most large specialized frugivores are absent howlers may be the main seed disperser of large fruits.